Nigerian motor vehicle traffic, an economic forecast - Hogg, V. W.; Roelandts, C. M. ([London] Published for the Nigerian Institute of Social and Economic Research [by] Oxford University Press, 1962)
The author's objective is to estimate Nigeria's motor vehicle population in the year 1968. Their estimate is described as an exercise in methodology rather than one in the mathematical certainties; and where assumptions have had to be made, the have tried to state clearly what these are
Includes index
osc 29/01/2019
Loans
Keywords: Traffic surveys